Acute renal infarction and cardioembolic stroke in a patient with atrial fibrillation and hyperthyroid-induced cardiomyopathy: a case report. (December 2016) - Adhikari, Samaj; Paudel, Kumar; Pandit, Kamal; Thapa, Shovit; Gajurel, Bikram; Dahal, Khagendra
Abstract Background Acute renal infarction is a rare entity with varied misleading manifestations resulting in diagnostic delay, misdiagnosis, and treatment leading to renal damage. Case presentation We report the case of a 28-year-old Dalit Nepalese man who presented with sudden onset occipital headache and later developed severe left flank pain. He was diagnosed with posterior cerebral infarction with hemorrhagic transformation and a subsequent acute renal infarction with atrial fibrillation and hyperthyroid-induced cardiomyopathy. He was managed with oral anticoagulant and antithyroid drug. Conclusion A high index of suspicion of acute renal infarction is required in patients with risk factors of thrombosis presenting sudden onset flank pain.